Dietary habits, physical activity, and self-reported rhinosinusitis in children and adolescents - Pazdro-Zastawny, Katarzyna; Krajewska, Joanna; Kolator, Mateusz; Basiak-Rasała, Alicja; Górna, Sara; Zatoński, Tomasz (Frontiers in Public Health, 2024)
Background Pediatric paranasal rhinosinusitis is one of the more common pediatric diseases of the upper respiratory tract and it entails significant morbidity. Most commonly, it is caused by a viral infection of the nasal mucosa, which spreads through the natural passages within the cavities of the paranasal sinuses, leading to inflammation of the mucosa that lines the nasal cavity and paranasal sinuses. Methods The objective of this cohort study was to assess whether there is a correlation between pediatric rhinosinusitis, physical activity, and selected dietary habits among pupils aged 6 to 16 years from elementary schools in Wrocław, Poland. This study – as part of the pro-health program “Let us Get the Kids Moving” – is also aimed at establishing factors that potentially predispose children to developing RS. The survey study was conducted on a group of 2,458 children and adolescents from elementary schools in Wrocław. The age of the examined children ranged from 6 to 17 years (mean = 10.8 years; standard deviation = 2.7). Results Rhinosinusitis was more common in the children aged 13–17 years than in those aged 6–9 years (6.4% vs. 1.5%; p < 0.001) or 10–12 years (6.4 vs. 2.6%; p < 0.001). The study revealed a significant positive correlation between rhinosinusitis development and several variables: age > 11 years, attending swimming classes fewer than 1–2 times a week, using a computer, consuming milk, salty snacks, and carbonated sweet drinks, consuming fruit fewer than 1–2 times a week, not attending physical education classes, eating fewer than 4 meals, and not eating breakfast at home (p < 0.05). Conclusion It is of great importance to establish preventive measures against recurrent upper respiratory tract infections that may predispose children to rhinosinusitis. Introducing healthier, traditional dietary habits and regular physical activity in children and adolescents may result in normal and adequate immune response and proper functioning of the inflammatory control system.